Toll-Like Receptor-4 Mediated Inflammation Is Involved in the Cardiometabolic Alterations Induced by Intermittent Hypoxia - Laureline Poulain; Vincent Richard; Patrick Lévy; Maurice Dematteis; Claire Arnaud (Mediators of Inflammation)
Objective. Intermittent hypoxia (IH) is a major component of sleep apnea syndrome as its cardiometabolic complications have been mainly attributed to IH. The pathophysiology is still poorly understood but there are some similarities with the obesity-associated cardiometabolic complications. As the latter results from inflammation involving toll-like receptor-4 (TLR4) signaling, we assessed this pathway in the cardiometabolic consequences of IH. Methods. Lean adult male TLR4-deficient (TLR4−/−) mice and their controls (C57BL/6 mice) were exposed to either IH (FiO2 21-5%, 1 min cycle, 8 h/day) or air (normoxic mice) for 4 weeks. Animals were assessed at 1-week exposure for insulin tolerance test and after 4-week exposure for morphological and inflammatory changes of the epididymal fat and thoracic aorta. Results. IH induced insulin resistance, morphological and inflammatory changes of the epididymal fat (smaller pads and adipocytes, higher release of TNF-α and IL-6) and aorta (larger intima-media thickness and higher NFκB-p50 activity). All these alterations were prevented by TLR4 deletion. Conclusion. IH induces metabolic and vascular alterations that involve TLR4 mediated inflammation. These results confirm the important role of inflammation in the cardiometabolic consequences of IH and suggest that targeting TLR4/NFκB pathway could represent a further therapeutic option for sleep apnea patients.